The 100th Anniversary of the Republic of Türkiye: Current Dynamics and Future Prospects in Nigeria-Türkiye Relations - Okolie, Ugo Chuks; Nwokolobia, Anthony C. (Master Program of Sociology, Universitas Malikussaleh,, 2024)
The formulation, adoption and implementation of appropriate trade-oriented economic policies have become imperative as an indispensable tool for stimulating and regulating trade development process. A more favorable trade negotiation position combined with sound political, macroeconomic and infrastructural policy frameworks is the best route to stimulating trade performance and reaps the benefits of fuller participation in the global trading system. In light of this, this paper examines potential future areas of stronger collaboration between Nigeria and Türkiye and presents specific policy recommendations. In particular, the paper contributes to economic policy-making efforts in terms of current dynamics and future prospects of increased bilateral relations. Also, Türkiyes policy and specific initiatives toward the African continent was discussed. The new atmosphere of the 100th anniversary of the republic of Türkiye notwithstanding the controversy about its orientation, including those toward Africa connected with the goal of establishing hegemony, economic and political investments in Nigeria would bring about a new momentum to bilateral relations. In conclusion, in their search for alternative export markets, Turkish exporters now consider that Nigeria has great potential for meeting their economic interests. This paper therefore is a wakeup call that will advance the economic and political co-operation between Türkiye and Nigeria going forward.